KLASSIKALÍQ TEŃSIZLIKLERDI DÁLILLEWDE TRANS TEŃSIZLIGIN QOLLANÍW USÍLLARÍ - Kalekeeva, T.T.; Shamenova, J. (SCIENCE and SOCIETY, 2022)
The article discusses methods for proving classical inequalities using Cauchy’s inequalities with respect to the mean, inequalities between geometric and harmonic means, inequalities between quadratic and arithmetic means, Cauchy-Bunyakovsky-Schwarz inequalities, Shebichev’s inequalities.